Nurses knowledge and practice regarding post-operatives pain management in orthopedic ward at Hospital Universiti Sains Malaysia (Hospital USM) - Sokor, Nurul Anati Ahmad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
The purpose of this descriptive study was to determine nurses' knowledge and practice levels regarding post-operatives pain management in orthopaedic ward at Hospital USM. Nurses of all three orthopaedic wards in Hospital USM were recruited. A descriptive cross sectional study was conducted on 40 nurses in three orthopaedic wards. Data was obtained using self-administered questionnaire were consist of three parts, Part A (demographic data), Part B (knowledge) and Part C (clinical practice). Three experts tested the content validity of instruments, and the reliability obtained by Cronbach 's alpha coefficients were 0.60 and 0.60 by Kuder-Richardson formula respectively. The data were analysed with SPSS version 20.0, using descriptive statistic statistic, ANOVA for answering the research questions. The result showed the majority of the nurses (97.5%) had high level of knowledge and practice (95%). One-way ANOV A revealed that there was difference between years of working and knowledge (p=0.048)while no difference between clinical practice (p=0.528). In conclusion, the findings of this study will provide guideline for nurses to improve the nurses' knowledge and practice regarding post-operatives pain management.